2023
DOI: 10.1155/2023/8700302
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, Mortality, and Clinical Outcomes of Hospitalized Patients with COVID-19 and Diabetes: A Reference Single-Center Cohort Study from Poland

Abstract: Background. Diabetes is a risk factor for a severe course of COVID-19. We evaluated the characteristics and risk factors associated with undesirable outcomes in diabetic patients (DPs) hospitalized due to COVID-19. Materials and Methods. The data analysis of patients admitted between March 6, 2020, and May 31, 2021, to the University Hospital in Krakow (Poland), a reference center for COVID-19, was performed. The data were gathered from their medical records. Results. A total number of 5191 patients were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
1
1
1
Order By: Relevance
“…These numbers should be seen in the context that initially, due to a mandatory supervision by epidemiological services or hospitalization related to COVID-19, the number of patients admitted to the hospitals was disproportionately higher, as hospitalization of all patients with SARS-CoV-2 infection was obligatory ( 25 ). Of note, the proportion of DPs among all hospitalized COVID-19 patients identified on the state level was slightly lower than in our earlier report involving a large single center cohort from the University Hospital in Krakow (26,3%) ( 26 ). Still, multiple reasons may contribute to the higher frequency of hospitalizations in patients with comorbidities, including diabetes.…”
Section: Discussioncontrasting
confidence: 74%
“…These numbers should be seen in the context that initially, due to a mandatory supervision by epidemiological services or hospitalization related to COVID-19, the number of patients admitted to the hospitals was disproportionately higher, as hospitalization of all patients with SARS-CoV-2 infection was obligatory ( 25 ). Of note, the proportion of DPs among all hospitalized COVID-19 patients identified on the state level was slightly lower than in our earlier report involving a large single center cohort from the University Hospital in Krakow (26,3%) ( 26 ). Still, multiple reasons may contribute to the higher frequency of hospitalizations in patients with comorbidities, including diabetes.…”
Section: Discussioncontrasting
confidence: 74%
“…Same findings were reported by a study done in Kuwait [18] . Mortality rate in our study was higher than the reported rate for the UAE [19] and in concordance with another study by kumar A et al, [7] and other studies also [20,21] . Diabetes mellitus was found to negatively impact most of the outcomes analyzed in our study like hospital stay, ICU admission, and mortality were all adversely influenced by the presence of diabetes among covid-19 patients.…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were reported in a Chinese study in which DM patients with COVID-19 were found to have a 2.95-fold increased risk of death compared to non-diabetics [ 31 ]. Data from other countries also show higher mortality in COVID-19 patients in the presence of DM, including Scotland [ 32 ], Poland [ 33 ], and Saudi Arabia [ 34 ]. A meta-analysis comprising seven studies revealed DM as a significant risk factor for suffering from a severe course of COVID-19 infection, with an increased relative risk of 2.11-fold compared to non-diabetic COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%